Csf2ra deletion attenuates acute lung injuries induced by intratracheal inoculation of aerosolized ricin in mice - Zong, Fuliang; Li, Sha; Wang, Yifeng; Xiao, Nan; Deng, Mengyun; Zhang, Zhipeng; Su, Duo; Gao, Bo; Zhou, Dongsheng; Hu, Lingfei; Yang, Huiying (Frontiers in Immunology, 2022)
Specific therapeutics are not available for acute lung injury (ALI) induced by ricin toxin (RT). Inhibiting the host immune response in the course of pulmonary ricinosis is hypothesized to be of benefit and can be achieved by impairing granulocyte-macrophage colony-stimulating factor (GM-CSF) signaling, thereby reducing the pro-inflammatory response to exogenous foreign body invasion. However, it is unknown whether mice with impaired GM-CSF signaling can survive after RT inhalation. To test this, Csf2ra knockout (KO) mice that lack GM-CSF signaling and wild-type (WT) mice models of intratracheal exposure to a lethal dose (2× LD50) of RT were established. Survival was greater in Csf2ra KO mice 14 days after RT inhalation compared with WT mice. Highly co-expressed genes that probably attenuated the pro-inflammatory response in the lung of Csf2ra KO mice were identified. Bioinformatics analysis revealed that transcriptome changes involved mostly inflammation-related genes after RT exposure in both Csf2ra KO mice and WT mice. However, the levels of pro-inflammatory pathways, such as the TNF signaling pathway and NF-kappa B signaling pathway, in Csf2ra KO mice are significantly decreased and the speed of neutrophil chemotaxis and recruitment inhibited after RT-exposure relative to WT mice. RT-qPCR and flow cytometry validated results of RNA-Seq analysis. This work provides potential avenues for host-directed therapeutic applications that mitigate the severity of ALI-induced by RT.